Experimental investigations on current and temperature imbalances among parallel-connected lithium-ion cells at different thermal conditions - Fill, Alexander; Mader, Tobias; Schmidt, Tobias; Avdyli, Arber; Kopp, Mike; Birke, Kai Peter (Journal of Energy Storage, 2022)
In this article the influence of Cell to Cell Variances (CtCV) and the thermal design of the battery on electrical and thermal cell imbalances are experimentally investigated for different cell configurations. Measurements with six cell groups are conducted, four cell groups with two parallel cells holding different CtCV and one cell group each with three and four parallel cells. In order to emulate different thermal conditions within a battery, the cells are separated locally and clamped between temperature-controllable aluminum plates. Due to this setup different conditions and battery system components can be emulated, such as insulation material, an adjacent cell or the battery housing. Asides from full discharge/charge cycles with constant current, the relaxation behavior and isolated selective current pulses are considered. It is found that the current inhomogeneity is superimposed by two effects: the voltage source difference ΔUsc and the reciprocal resistance ratio R2/(R1+R2), with the resistance of cell 1 R1 and cell 2 R2. The full discharge/charge cycles with constant current leading to a build up of ΔUsc acting against the resistance ratio. In case of subsequent relaxation, only ΔUsc is effective, since the resistance term is multiplied by the battery current IBatt. By applying an inversely directed pulse, ΔUsc and R2/(R1+R2) act in the same direction.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Current and temperature imbalance; Current distribution; Lithium-ion battery; Parallel-connected cells